Pelatihan Mikrokontroler Dasar Arduino UNO dan Simulasi Tinkercad - Gideon Manalu, Ferry Rippun; Wijayanti, Linda; Mulyadi, Melisa; Ghozali, Theresia; Sereati, Catherine Olivia; Kartawidjaja, Maria Angela (Program Studi Teknik Industri, Fakultas Teknik, Universitas Katolik Indonesia Atma Jaya Jakarta, 2024)
The Electrical Engineering study program of the Faculty of Engineering, Atma Jaya Catholic University of Indonesia has been collaborating with Harapan Bagi Bangsa Christian Middle School, Cilincing, North Jakarta for several years in an extracurricular program for junior high school students, as a form of community service from Electrical Engineering lecturers. The extracurricular activity program implemented is in the form of basic electronics training. The theme of the activity varies, according to the requests and needs of the partner schools. The first activity is to provide basic electronics skills training to students. This program received a very positive response from teachers and students. From the evaluation results of previous activities, all students wanted training activities with advanced materials. The training provided is an introduction to basic Arduino Uno microcontrollers using Tinkercad simulation software. The purpose of this activity is to conduct training on the introduction and how to program the Arduino Uno microcontroller to turn on Light Emitting Diodes (LEDs). The training was carried out at Harapan Bagi Bangsa Christian Middle School. The training began by assembling the resistor and LED components on the project board. After all the components were installed, an Arduino Uno microcontroller program was created to turn on the LEDs alternately according to the order of the program created. The training used Tinkercad simulation software and the Arduino Uno microcontroller board. From the results of the student evaluation, 92.2% of students gave good and excellent ratings, while 7.8% gave neutral ratings for this training.